POLITICAL EDUCATION OF MADRASAH IN THE HISTORICAL PERSPECTIVE - Hamruni Hamruni; Syamsul Kurniawan (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2018)
Reading the history of its development in Indonesia, the madrasa emerged from a growing concept in response to the attitude of modernizing pesantren away from it. However, the flow of madrasah is a trend of withdrawal trends, and the impression is less progressive. Many people appear in the community, who assume madrasa as an outdated educational institution and synonymous with underdevelopment. However, a small number of others assume the opposite. The focus of this article is to answer the question of why madrasas in their development in Indonesia are increasingly showing less progressive symptoms? How did the government build the madrasa? And how to work on madrasas in Indonesia that are fostered and developed. This article is written departing from library research, about the politics of education towards madrasa in a historical perspective in Indonesia.